Bucking Policy Optimization of Teak Log to Increase the Revenue of KPH Madiun. - Wahyu Andayani; Ris Hadi Purwanto; Slamet Riyanto (Jurnal Ilmu Kehutanan)
The revenue of KPH Madiun could have been effectively increased through improvement in its bucking policy implementation. Such implementation had been formulated in this research using optimization theory to generate the maximum total economic values of log assortments cut from felled trees. As teakwood production had been the core business, contributing more than 50 % of the revenue, KPH Madiun Perum Perhutani Unit II East Java had been choosen as the object and location of this research. The research found and analized 96 alternatives of bucking policy implementations, derived from 6 possible diameter classes, and 16 possible assortment quality classes. The log assortment was identified by its diameter, length, and quality, as raw materials of veneer, parquet, and local industry. Through optimization process, the optimum bucking policy could potentially increase revenue of KPH Madiun to the maximum of IDR 4,599,460 per m3, or IDR 8,921,623 per tree of 1.94 m3 average. Comparing to existing revenue of IDR 3,701,503 per m3, or IDR 7,179,847 per tree of the same average, which has been based on the formal bucking policy guidance of um Perhutani Unit II (2006), it could be a significant potential increase of 24.26 % or equal to 1.94 m3.